Using virtual learning environment in a call center for effective responses in COVID-19 pandemic context - Díaz, Francisco Javier (2020)
The Phone Line 148 (in spanish, Centro de Atencion Integral Telefonica-linea 148, CAIT) of the de Government of Province of Buenos Aires (Argentina) is the telephone communication channel with citizens for consultations about general provincial procedures. During the COVID-19 pandemic, the phone line 148 is one of the first contacts between a person that believes to be infected and the Health Care System. It is the principal place of the registry of suspected cases of infection and close contact cases. In addition, it provides general information about situations related to the pandemic. The use of a virtual learning tool as Moodle, facilitated the formation of a community to establish a uniform discourse before citizens and guarantee immediate communication in the face of new guidelines or emerging situations.